2021
DOI: 10.2147/hiv.s323090
|View full text |Cite|
|
Sign up to set email alerts
|

Levels of Adherence and Associated Factors Among Children on ART Over Time in Northwest, Ethiopia: Evidence from a Multicenter Follow-Up Study

Abstract: Background Despite the increased availability of antiretroviral therapy (ART), its success depends on a high level of adherence to a life-long antiretroviral therapy. However, the extent and factors associated with adherence to ART are not well known, especially in the current study setup. Therefore, this study aimed to assess the level of adherence and associated factors among children on ART in Northwest, Ethiopia. Methods A retrospective follow-up study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
(39 reference statements)
2
10
1
Order By: Relevance
“…Research evidence indicates that experiencing side effects associated with a given medication leads to poor adherence [36]. Consistent with previous studies [15,37,38], we found that, compared to the Tenofevir-based regimen, non-adherent children had a higher odds of receiving Zidovudine-and Abacabir-based regimens.…”
Section: Discussionsupporting
confidence: 90%
“…Research evidence indicates that experiencing side effects associated with a given medication leads to poor adherence [36]. Consistent with previous studies [15,37,38], we found that, compared to the Tenofevir-based regimen, non-adherent children had a higher odds of receiving Zidovudine-and Abacabir-based regimens.…”
Section: Discussionsupporting
confidence: 90%
“…As far as our knowledge is concerned, there is a shortage of regional wide research done recently on factors affecting the development of TB among HIV-infected adults under HAART in the study area. 12 Therefore, this research has been conducted with the objective to investigate factors affecting the development of TB among HIV patients under treatment followed in 17 government hospitals in the region. The current investigation also aimed to triangulate whether previously identified factors in developed countries also worked in the study area (low-income country).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to other studies, ART adherence among Swati adolescents was higher than in studies conducted among ALHIV in South Africa (65%), Kenya (76%) and Zimbabwe (28%) while comparable with studies conducted in Nigeria (85%), Uganda (80%), Cameroon (83%) [10,16,22,3840]. These discrepancies among the countries could be due to the differences in outcome measurements, settings, sample sizes, and study designs as explained in a study conducted in Ethiopia among children on ART [21].…”
Section: Discussionmentioning
confidence: 72%
“…Several factors associated with ART adherence have been identified among studies. These include age, sex, missing clinical appointment, presence of opportunistic diseases, duration on ART, ART regimen, family support, type of health facility, World Health Organization (WHO) clinical staging, VLS, and CD4-count [10,18,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%